Respostas

2014-08-19T00:07:45-03:00
A) x ( x - 3 ) - 2 ( x - 3 ) = 6
x² - 3x - 2x + 6 - 6 = 0
x² -5x = 0
x ( x - 5 ) = 0
x = 0
x - 5 = 0
x = 5


B ) ( x + 5 )² = 25
( x + 5 ) ( x + 5 ) = 25
x² + 5x + 5x + 25 - 25 = 0
x² + 10x = 0
x ( x + 10 ) = 0
x = 0
x + 10 = 0
x = - 10


C ) ( x - 2 ) ² = 4 - 9x
( x - 2 ) ( x - 2 ) = 4 - 9x
x² - 2x - 2x + 4 - 4 + 9x = 0
x² + 5x = 0
x ( x + 5 ) = 0
x = 0
x + 5 = 0
x = - 5

D ) ( x + 1 ) ( x - 3 ) = - 3
x² - 3x + x - 3 + 3 = 0
x² - 2x = 0
x ( x - 2 ) = 0
x = 0
x - 2 = 0
x = 2


E ) 2x² = 8x
2x² - 8x = 0
2x ( x - 4 ) = 0
2x = 0
x = 0/2
x = 0
x - 4 = 0
x = 4